Physiological and biochemical effects of 2.4-D herbicide in wheat (Triticum aestivum L.) varieties - Gülengül, Songül Çanakcı; Karabulut, Fadime (Bitlis Eren Üniversitesi, 2021)
In this work were investigated the physiological and biochemical responses depended on toxic effect caused by different concentrations of herbicides called as 2.4-Dichlorophenoxyacetic acid (2.4-D) herbicide in the seedlings that belong to three wheat varieties. The seeds which belong to wheat (Triticum aestivum L. Bayraktar cv., İkizce cv. and Tosunbey cv.) were used as plant material. 15-day old seedlings for each wheat variety were divided into 4 groups consisting of the same number of seedlings and four variety doses of herbicide (0, 100 µM, 300 µM ve 1000 µM) were applied for them. In these applications for seedlings was preferred hydroponic surrounding to root. Although three varieties increased the growth of root and shoot elongation from the growth parameters of the seedlings, it leaded to a decrease in growth parameters in general in this herbicide. Although 2.4-D in the leaves caused an increase in 100 ?M dose for only the Bayraktar in amount of chlorophyll a+b. In ones except these, there has always been a decreased. The amount of carotenoid resulted in the reduction of three varieties. Amount of MDA increased in all three varieties. Glutathione (GSH) / oxidized glutathione (GSSG) ratios in leaves increased in three varieties. The superoxide dismutase (SOD) activity in the leaves increased at the Bayraktar and decreased in the İkizce and the Tosunbey. Catalase (CAT) activity showed to a decrease in three varieties. As a result, it was determined that the 2.4-D, which was toxic for wheat plants even in very low concentrations.